Impact of Environmental Education on Beginning Preservice Teachers' Environmental Literacy. (20th April 2018) - Dada, Deborah O.; Eames, Chris; Calder, Nigel
Abstract: One of the goals of environmental education is the development of environmental literacy. The development of environmental literacy for preservice teachers is critical if they are to be confident and competent to deliver environmental education in schools. Little is known about the impact of environmental education on preservice teachers' environmental literacy and their subsequent practices as teachers within schools in New Zealand. This study used a mixed-methods approach with a pretest and posttest design to examine the environmental literacy of preservice teachers enrolled in a compulsory environmental education paper as part of their Bachelor of Teaching program at a New Zealand university. The perceptions of the preservice teachers' preparedness to teach environmental education was also examined. Findings indicate that despite only slight shifts in preservice teachers' environmental literacy, their confidence to teach environmental education significantly increased after completing the paper. Increases in the strength of correlations between environmental knowledge and affective dispositions were observed upon completing the environmental education paper. Implications of findings for teacher education programs are discussed. This study could inform curriculum design and teaching and learning practices for effectively preparing preservice teachers to promote the development of the environmental literacy of students in their future schools.